Antinociceptive and antiinflammatory activities of the aqueous extract of Trigonopleura malayana resin in experimental animal models. - Sulaiman, Mohd Roslan; Zakaria, Zainul Amiruddin; Kamaruddin, Anita; Teoh, Fei Meng; Israf Ali, Daud Ahmad; Moin, Saidi (Prous Science, 2008)
Trigonopleura malayana L. (Euphorbiaceae) resin, locally known as Gambir Sarawak, has been used traditionally to alleviate pain associated with insect bites, muscle ache, toothache and minor injuries. The present study was carried out using various animal models to determine the antinociceptive and antiinflammatory activities of the T. malayana resin aqueous extract. Antinociceptive activity was measured using the abdominal constriction, hot plate and formalin tests, while antiinflammatory activity was measured using the carrageenan-induced paw edema test. The extract, obtained after 24 h of soaking the dried resin in distilled water, was prepared in doses of 0.3, 3 and 10 mg/kg and administered subcutaneously 30 min prior to the assays. The mechanism of action was also determined by prechallenging with naloxone (10 mg/kg), a nonselective opioid antagonist. The extract was found to exhibit significant (P < 0.05) and dose-dependent antinociceptive and antiinflammatory activities; naloxone failed to inhibit the former activity. In conclusion, the aqueous extract of T. malayana resin possesses nonopioid antinociceptive and antiinflammatory activities, thus supporting previous claims regarding its traditional use by the Malays to treat various ailments, particularly those related to pain.